Laser holographic film and preparation method thereof
By introducing rare earth elements and quaternary ammonium salt Gemini surfactant into the sol-gel method, the rare earth doped nanotitanium dioxide film was prepared, which solved the problem of low refractive index of nanotitanium dioxide films, and improved the anti-counterfeiting effect and density of laser holographic films. .
Patent Information
- Application Number
- CN202411811164.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-07
AI Technical Summary
The refractive index of existing nanotitanium dioxide films is generally low, which is difficult to meet the anti-counterfeiting needs of laser holographic films. Moreover, the films prepared by the sol-gel method are not dense, which affects the anti-counterfeiting effect.
The rare earth doped nanotitanium dioxide film was prepared by sol-gel method. The TiO2 grains were refined by introducing rare earth elements, combined with quaternary ammonium salt Gemini surfactant, and the electric double layer was formed, which reduced surface tension and increased the density and refractive index of the film. .
The refractive index of the information layer is improved, the anti-counterfeiting effect of the laser holographic film is enhanced, and the reflection rate and stability are achieved.
Smart Images

Figure CN119274428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of laser holographic films, in particular to a laser holographic film and a preparation method thereof. Background Art
[0002] In recent years, the anti-counterfeiting labels widely used for products or commodities are opaque aluminum-plated laser holographic films made into small labels. This type of film is a mature industrial product and it is difficult to really play an anti-counterfeiting role. In production practice, aluminum-plated films are gradually replaced by high-refractive index transparent medium films such as nano-titanium dioxide films. These transparent medium films have better optical properties and anti-counterfeiting properties, which can further improve the anti-counterfeiting effect of laser holographic anti-counterfeiting films.
[0003] In the prior art, the main preparation methods of nano titanium dioxide films include physical vapor deposition (PVD) (evaporation, sputtering), chemical vapor deposition (CVD) and wet chemical methods (sol-gel method, etc.). Among them, although the nano titanium dioxide films prepared by physical vapor deposition and chemical vapor deposition have high refractive index, the required equipment is expensive and the deposition rate is low. The sol-gel method is simple to operate, fast and efficient, but the refractive index of the prepared nano titanium dioxide films is generally low, which is difficult to meet the anti-counterfeiting requirements of laser holographic films. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a laser holographic film and a preparation method thereof.
[0005] The technical solutions adopted are as follows: A method for preparing a laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template by laser micro-engraving and electroforming, the sol is prepared by sol-gel method, the sol is evenly coated on the base film layer by coating method, and then dried in a drying oven to obtain the information layer, and finally the grating stripes on the template are transferred to the information layer by hot pressing; The preparation method of the sol is as follows: Tetrabutyl titanate, rare earth nitrate and acetylacetone are dissolved in an alcohol solvent to obtain solution A, polyvinyl pyrrolidone and quaternary ammonium gemini surfactant are added into deionized water to obtain solution B, solution A is slowly added dropwise to solution B, and the pH of the mixed system is adjusted to 2-4 with concentrated hydrochloric acid, and the mixture is sealed and kept warm at 60-70°C for 6-12 hours; The mass ratio of the polyvinyl pyrrolidone to the quaternary ammonium salt gemini surfactant is 1-10:1-10; The preparation method of the quaternary ammonium salt gemini surfactant is as follows: N,N-dimethyl long-chain alkylamine, epichlorohydrin, concentrated hydrochloric acid and an organic solvent are mixed and reacted for 1-10 hours. After the reaction is completed, the organic solvent is removed by distillation under reduced pressure. The obtained product is extracted with water and petroleum ether, and the petroleum ether phase is collected and added with acetone for recrystallization.
[0006] Furthermore, the molar ratio of tetrabutyl titanate to rare earth nitrate is 10-100:1.
[0007] Furthermore, the number of carbon atoms in the alkyl long chain of the N,N-dimethyl long-chain alkylamine is ≥8.
[0008] Furthermore, the reaction is carried out under a microwave environment at a reaction temperature of 60-80°C.
[0009] The present invention also provides a laser holographic film, which consists of an information layer and a base film layer. The information layer is a rare earth doped nano titanium dioxide film, and the refractive index of the rare earth doped nano titanium dioxide film in the wavelength range of 400-1000nm is ≥1.9.
[0010] Furthermore, the material of the base film layer is any one or more of BOPP, LDPE, PET, and PA.
[0011] Furthermore, the rare earth is dysprosium and / or terbium.
[0012] Beneficial effects of the present invention: The invention provides a laser holographic film and a preparation method thereof. The sol-gel method is easy to form an amorphous porous and mesh structure. The amorphous structure often has a low refractive index, which is not conducive to the anti-counterfeiting demand of the laser holographic film. In order to achieve a predetermined reflectivity, the present application introduces rare earth elements when preparing nano-TiO2 sol by the sol-gel method. Rare earth element doping can refine TiO2 grains, thereby reducing the formation of film holes and mesh structures. The hydrophilic group of the quaternary ammonium salt gemini surfactant contains nitrogen atoms, which are easily adsorbed on the surface of the TiO2 colloid particles to form a double electric layer, which can effectively reduce the surface tension and improve the wetting effect of the sol and the base film layer. The multi-branched structure and the long alkyl chain make the sol have better stability. All of these are conducive to improving the density of the film, so that the information layer has a higher refractive index, and the anti-counterfeiting effect of the laser holographic film is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a curve showing the change of the refractive index of the information layer prepared in Example 1; Figure 2 is a curve showing the change of the refractive index of the information layer prepared in Example 2; Figure 3 is a curve showing the change of the refractive index of the information layer prepared in Example 3; Figure 4is a curve showing the change of the refractive index of the information layer prepared in Example 4; Figure 5 is a curve showing the change of the refractive index of the information layer prepared in Example 5; Figure 6 is a curve showing the change of the refractive index of the information layer prepared in Comparative Example 1; Figure 7 is a curve showing the change of the refractive index of the information layer prepared in Comparative Example 2; Figure 8 This is the refractive index variation curve of the information layer prepared in Comparative Example 3. DETAILED DESCRIPTION
[0014] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0015] Embodiment 1: A laser holographic film, consisting of an information layer and a BOPP base film layer, wherein the information layer is a Dy-doped nano-TiO2 film; The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.26 g N,N-dimethyloctylamine, 0.93 g epichlorohydrin, 5 ml concentrated hydrochloric acid and 30 ml isopropanol were added into a flask, stirred and mixed, and then subjected to microwave heating for 8 h, the microwave power was 400 W, and the reaction temperature was 75°C. After the reaction was completed, the isopropanol was removed by vacuum concentration, 50 ml deionized water and 50 ml petroleum ether were added, and stirred and extracted for 10 min. The petroleum ether phase was separated and concentrated under reduced pressure to about 15 ml, 150 ml acetone was added, and the mixture was stirred and crystallized at 0-5°C for 5 h, and then filtered. The product was collected and dried in vacuo to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate, 1.74 g (5 mmol) of dysprosium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium salt gemini surfactant were added to 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol, and the sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature is 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The drying tunnel temperature is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0016] The optical properties of the information layer of this embodiment are tested by a spectroscopic ellipsometer (the incident angle is 55° and 65°, the wavelength is 400-1000nm), and the refractive index variation curve is as follows: Figure 1 shown.
[0017] Embodiment 2: A laser holographic film, consisting of an information layer and a BOPP base film layer, wherein the information layer is a Tb-doped nano-TiO2 film; The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.26 g N,N-dimethyloctylamine, 0.93 g epichlorohydrin, 5 ml concentrated hydrochloric acid and 30 ml isopropanol were added into a flask, stirred and mixed, and then subjected to microwave heating for 8 h, the microwave power was 400 W, and the reaction temperature was 75°C. After the reaction was completed, the isopropanol was removed by vacuum concentration, 50 ml deionized water and 50 ml petroleum ether were added, and stirred and extracted for 10 min. The petroleum ether phase was separated and concentrated under reduced pressure to about 15 ml, 150 ml acetone was added, and the mixture was stirred and crystallized at 0-5°C for 5 h, and then filtered. The product was collected and dried in vacuo to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate, 1.73 g (5 mmol) of terbium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium gemini surfactant were added into 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60 ° C for 10 h to obtain a sol, and the sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature is 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The drying tunnel temperature is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0018] The optical properties of the information layer of this embodiment are tested by a spectroscopic ellipsometer (the incident angle is 55° and 65°, the wavelength is 400-1000nm), and the refractive index variation curve is as follows: Figure 2 shown.
[0019] Embodiment 3: A laser holographic film, consisting of an information layer and a BOPP base film layer, wherein the information layer is a Tb and Dy co-doped nano-TiO2 film; The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.26 g N,N-dimethyloctylamine, 0.93 g epichlorohydrin, 5 ml concentrated hydrochloric acid and 30 ml isopropanol were added into a flask, stirred and mixed, and then subjected to microwave heating for 8 h, the microwave power was 400 W, and the reaction temperature was 75°C. After the reaction was completed, the isopropanol was removed by vacuum concentration, 50 ml deionized water and 50 ml petroleum ether were added, and stirred and extracted for 10 min. The petroleum ether phase was separated and concentrated under reduced pressure to about 15 ml, 150 ml acetone was added, and the mixture was stirred and crystallized at 0-5°C for 5 h, and then filtered. The product was collected and dried in vacuo to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate, 0.87 g (2.5 mmol) of dysprosium nitrate, 0.865 g (2.5 mmol) of terbium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium gemini surfactant were added into 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol. The sol was evenly coated on a 100 mm thick glass plate by a coating method. The coating temperature is 80±5℃ on the BOPP base film layer of μm. After coating, the film coated with the information layer is sent to the drying tunnel. The temperature of the drying tunnel is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃, and one of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0020] The optical properties of the information layer of this embodiment are tested by a spectroscopic ellipsometer (the incident angle is 55° and 65°, the wavelength is 400-1000nm), and the refractive index variation curve is as follows: Figure 3 shown.
[0021] Embodiment 4: A laser holographic film, consisting of an information layer and a BOPP base film layer, wherein the information layer is a Dy-doped nano-TiO2 film; The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.42g N,N-dimethyl-n-nonylamine (instead of N,N-dimethyl-n-octylamine), 0.93g epichlorohydrin, 5ml concentrated hydrochloric acid and 30ml isopropanol were added into a flask, stirred and mixed, and then subjected to microwave heating for 8h, the microwave power was 400W, and the reaction temperature was 75°C. After the reaction, the isopropanol was removed by vacuum concentration, 50ml deionized water and 50ml petroleum ether were added, and stirred and extracted for 10min. The petroleum ether phase was separated, concentrated under reduced pressure to about 15ml, and 150ml acetone was added. The mixture was stirred and crystallized at 0-5°C for 5h, and then filtered. The product was collected and dried under vacuum to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate, 1.74 g (5 mmol) of dysprosium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium salt gemini surfactant were added to 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol, and the sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature is 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The drying tunnel temperature is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0022] The optical properties of the information layer of this embodiment are tested by a spectroscopic ellipsometer (the incident angle is 55° and 65°, the wavelength is 400-1000nm), and the refractive index variation curve is as follows: Figure 4 shown.
[0023] Embodiment 5: A laser holographic film, consisting of an information layer and a BOPP base film layer, wherein the information layer is a Dy-doped nano-TiO2 film; The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.7 g N, N-dimethyl-n-decylamine (instead of N, N-dimethyl-n-octylamine), 0.93 g epichlorohydrin, 5 ml concentrated hydrochloric acid and 30 ml isopropanol were added to a flask, stirred and mixed, and then subjected to microwave heating for 8 h, the microwave power was 400 W, and the reaction temperature was 75°C. After the reaction was completed, the isopropanol was removed by vacuum concentration, 50 ml deionized water and 50 ml petroleum ether were added, and stirred and extracted for 10 min. The petroleum ether phase was separated and concentrated under reduced pressure to about 15 ml, 150 ml acetone was added, and the mixture was stirred and crystallized at 0-5°C for 5 h, and then filtered. The product was collected and dried in vacuo to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate, 1.74 g (5 mmol) of dysprosium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium salt gemini surfactant were added to 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol, and the sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature is 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The drying tunnel temperature is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0024] The optical properties of the information layer of this embodiment are tested by a spectroscopic ellipsometer (the incident angle is 55° and 65°, the wavelength is 400-1000nm), and the refractive index variation curve is as follows: Figure 5 shown.
[0025] Comparative Example 1: The method is basically the same as Example 1, except that dysprosium nitrate is not added during the preparation of the information layer. A laser holographic film consists of an information layer and a BOPP base film layer, wherein the information layer is a nano-TiO2 film.
[0026] The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 3.26 g N,N-dimethyloctylamine, 0.93 g epichlorohydrin, 5 ml concentrated hydrochloric acid and 30 ml isopropanol were added into a flask, stirred and mixed, and then subjected to microwave heating for 8 h, the microwave power was 400 W, and the reaction temperature was 75°C. After the reaction was completed, the isopropanol was removed by vacuum concentration, 50 ml deionized water and 50 ml petroleum ether were added, and stirred and extracted for 10 min. The petroleum ether phase was separated and concentrated under reduced pressure to about 15 ml, 150 ml acetone was added, and the mixture was stirred and crystallized at 0-5°C for 5 h, and then filtered. The product was collected and dried in vacuo to obtain a quaternary ammonium gemini surfactant; 34 g (100 mmol) of tetrabutyl titanate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of quaternary ammonium gemini surfactant were added into 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60 ° C for 10 h to obtain a sol. The sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature was 8 0±5℃, after coating, the film coated with the information layer is sent to the drying tunnel, the temperature of the drying tunnel is maintained at 120±10℃, the residence time in the drying tunnel is 1min, and finally the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃, one of which is equipped with a template, and the film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0027] The optical properties of the information layer of this comparative example were tested by a spectroscopic ellipsometer (incident angles of 55° and 65°, wavelengths of 400-1000nm), and the refractive index variation curve was as follows: Figure 6 shown.
[0028] By comparison Figure 1 and Figure 6 It can be seen that the addition of dysprosium nitrate can increase the refractive index of the information layer.
[0029] Comparative Example 2: The method is basically the same as Example 1, except that no quaternary ammonium salt gemini surfactant is added during the preparation of the information layer; A laser holographic film consists of an information layer and a BOPP base film layer, wherein the information layer is a Dy-doped nano-TiO2 film.
[0030] The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 34 g (100 mmol) of tetrabutyl titanate, 1.74 g (5 mmol) of dysprosium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone was added to 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol. The sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The coating temperature was 200 °C. 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The temperature of the drying tunnel is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0031] The optical properties of the information layer of this comparative example were tested by a spectroscopic ellipsometer (incident angles of 55° and 65°, wavelengths of 400-1000nm), and the refractive index variation curve was as follows: Figure 7 shown.
[0032] By comparison Figure 1 and Figure 7 It can be seen that the addition of quaternary ammonium gemini surfactant during the preparation of the information layer plays a positive role in improving the refractive index of the information layer.
[0033] Comparative Example 3: The method is basically the same as Example 1, except that CTAB (hexadecyltrimethylammonium bromide) is used instead of the quaternary ammonium salt gemini surfactant when preparing the information layer; A laser holographic film consists of an information layer and a BOPP base film layer, wherein the information layer is a Dy-doped nano-TiO2 film.
[0034] The preparation method of the above laser holographic film is as follows: The grating stripes reflecting the holographic image are engraved on the template in advance by laser micro-engraving and electroplating; 34 g (100 mmol) of tetrabutyl titanate, 1.74 g (5 mmol) of dysprosium nitrate and 5 g of acetylacetone were dissolved in 100 ml of ethanol to obtain solution A. 1 g of polyvinyl pyrrolidone and 1 g of CTAB were added into 120 ml of deionized water to obtain solution B. Solution A was slowly added dropwise to solution B, and the pH of the mixed system was adjusted to 3 with concentrated hydrochloric acid. The mixture was sealed and kept warm at 60°C for 10 h to obtain a sol. The sol was evenly coated on a BOPP base film layer with a thickness of 100 μm by a coating method. The cloth temperature is 80±5℃. After coating, the film coated with the information layer is sent to the drying tunnel. The temperature of the drying tunnel is maintained at 120±10℃. The residence time in the drying tunnel is 1min. Finally, the information layer with a thickness of 1±0.1μm is hot pressed. The hot pressing is carried out between two pressure rollers. The pressure of the rollers on the film is 0.3±0.1MPa. The pressure rollers are heated to 90±5℃. One of them is equipped with a template. The film passes between the two pressure rollers. Under the action of this pressure and temperature, the grating stripes on the template are copied to the information layer.
[0035] The optical properties of the information layer of this comparative example were tested by a spectroscopic ellipsometer (incident angles of 55° and 65°, wavelengths of 400-1000nm), and the refractive index variation curve was as follows: Figure 8 shown.
[0036] By comparison Figure 1 and Figure 8 It can be seen that compared with CTAB, adding quaternary ammonium gemini surfactant during the preparation of the information layer can greatly improve the refractive index of the information layer.
[0037] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a laser holographic film, characterized in that: The details are as follows: The grating stripes reflecting the holographic image are engraved on the template by laser micro-engraving and electroforming, the sol is prepared by sol-gel method, the sol is evenly coated on the base film layer by coating method, and then dried in a drying oven to obtain the information layer, and finally the grating stripes on the template are transferred to the information layer by hot pressing; The preparation method of the sol is as follows: Tetrabutyl titanate, rare earth nitrate and acetylacetone are dissolved in an alcohol solvent to obtain solution A, polyvinyl pyrrolidone and quaternary ammonium gemini surfactant are added into deionized water to obtain solution B, solution A is slowly added dropwise to solution B, and the pH of the mixed system is adjusted to 2-4 with concentrated hydrochloric acid, and the mixture is sealed and kept warm at 60-70°C for 6-12 hours; The mass ratio of the polyvinyl pyrrolidone to the quaternary ammonium salt gemini surfactant is 1-10:1-10; The preparation method of the quaternary ammonium salt gemini surfactant is as follows: N,N-dimethyl long-chain alkylamine, epichlorohydrin, concentrated hydrochloric acid and an organic solvent are mixed and reacted for 1-10 hours. After the reaction is completed, the organic solvent is removed by distillation under reduced pressure. The obtained product is extracted with water and petroleum ether, and the petroleum ether phase is collected and added with acetone for recrystallization.
2. The method for preparing a laser holographic film according to claim 1, characterized in that: The molar ratio of tetrabutyl titanate to rare earth nitrate is 10-100:
1.
3. The method for preparing a laser holographic film according to claim 1, characterized in that: The number of carbon atoms in the alkyl long chain of the N,N-dimethyl long-chain alkylamine is ≥8.
4. The method for preparing a laser holographic film according to claim 1, characterized in that: The reaction is carried out under a microwave environment at a temperature of 60-80°C.
5. A laser holographic film prepared by the method for preparing a laser holographic film according to any one of claims 1 to 4, characterized in that: It consists of an information layer and a base film layer. The information layer is a rare earth doped nano titanium dioxide film. The refractive index of the rare earth doped nano titanium dioxide film in the wavelength range of 400-1000nm is ≥1.
9.
6. The laser holographic film according to claim 5, characterized in that: The material of the base film layer is any one or more of BOPP, LDPE, PET and PA.
7. The laser holographic film according to claim 5, characterized in that: The rare earth is dysprosium and / or terbium.
Citation Information
Patent Citations
Method for preparing rare-earth ultraviolet-resistant film by sol-gel method
CN102765888A
Light wave conversion-antireflection difunctional sol material and preparation method of thin film thereof
CN103058529A
Laser holographic anti-counterfeiting film and preparation method thereof
CN113442627A
Preparation method of nano TiO2-based particles meeting multi-target requirements based on machine learning optimization
CN117476121A